A matter of quantity: Common features in the drought response of transgenic plants overexpressing HD-Zip I transcription factors - Romani, Facundo Alihuen (2016)
Plant responses to water deficit involve complex molecular mechanisms in which transcription factors have key roles. Previous reports ectopically overexpressed a few members of the homeodomain-leucine zipper I (HD-Zip I) family of transcription factors from different species, and the obtained transgenic plants exhibited drought tolerance which extent depended on the level of overexpression, triggering diverse molecular and physiological pathways. Here we show that most HD-Zip I genes are regulated by drought in the vegetative and/or reproductive stages. Moreover, uncharacterized members of this family were expressed as transgenes both in Col-0 and rdr6-12 backgrounds and were able to enhance drought tolerance in host plants. The extent of such tolerance depended on the expression level of the transgene and was significantly higher in transgenic rdr6-12 than in Col-0. Comparative transcriptome analyses of Arabidopsis thaliana plants overexpressing HD-Zip I proteins indicated that many members have common targets. Moreover, the water deficit tolerance exhibited by these plants is likely due to the induction and repression of certain of these common HD-Zip I-regulated genes. However, each HD-Zip I member regulates other pathways, which, in some cases, generate differential and potentially undesirable traits in addition to drought tolerance. In conclusion, only a few members of this family could become valuable tools to improve drought-tolerance.